Optimizing the effect of tramp elements on intermetallic phases in HPDC Al alloys – A thermodynamic approach - Ishøy, Nicklas Kaas (My University, 2025)
The growing interest in increasing the recycled content of aluminium for highpressure die casting (HPDC) is driven by a demand for greater sustainability, as recycled content offers a ∼nearly 95% reduction in energy compared to primary aluminium. However, elevated levels of elemental contamination from recycled content, mainly tramp elements such as iron (Fe) and manganese (Mn), pose significant challenges. This thesis focuses on the thermodynamic analysis of the Al-Si-Fe-Mn system with additions of magnesium (Mg) by using Thermo-Calc through CALPHAD-based Scheil simulations at a high rate of 100 K/s, in conjunction with validation using complementary microstructure analysis. The simulations, comprising over 300 compositions, demonstrated a strong linear correlation between increasing Fe content and the fraction of the β-Al5FeSi phase. In contrast, increasing Mn content suppresses β phase formation by promoting the more benign α-Al15(MnFe)3Si2 phase. Si notably altered the solidification range and eutectic transitions within the system. Higher Mg levels led to phase competition between π-AlFeMgSi and β phases. The potential evaporation of Mg was also found to shift phase equilibria, increasing the fraction of β phase, emphasising the need for accuracy control of alloy compositions. Microstructure analysis, employing SEM and EDS on the cast alloys, shows that Fe influences β-intermetallics, as it is composed of Fe instead of Mn. The analysis also reveals compositional variations that influence kinetic effects, such as the formation of the δ-AlFeSi phase and localised solute depletion zones around α-phase particles. These findings clarify the effects of Fe, Mn, Si, and Mg on intermetallic phase formation and emphasise the importance of integrating kinetic effects to contribute to a more comprehensive understanding of optimising recycled aluminium alloys.
Keywords: recycled aluminium; Scheil simulation; HPDC; Thermo-Calc; intermetallic phases; CALPHAD